Action research for climate change adaptation : (Routledge, 2015)
Governments all over the world are struggling with the question of how to adapt to climate change. They need information not only about the issue and its possible consequences, but also about feasible governance strategies and instruments to combat it. At the same time, scientists from different social disciplines are trying to understand the dynamics and peculiarities of the governance of climate change adaptation.This book demonstrates how action-oriented research methods can be used to satisfy the need for both policy-relevant information and scientific knowledge. Bringing together eight case studies that show inspiring practices of action research from around the world, including Australia, Denmark, Vietnam and the Netherlands, the book covers a rich variety of action-research applications, running from participatory observation to serious games and role-playing exercises. It explores many adaptation challenges, from flood-risk safety to heat stress and freshwater availability, and draws out valuable lessons about the conditions that make action research successful, demonstrating how scientific and academic knowledge can be used in a practical context to reach useful and applicable insights. The book will be of interest to scholars and students of climate change, environmental policy, politics and governance.